Size, Trend, and Policy Implications of the Underground Economy - Renzo Orsi; Davide Raggi; Francesco Turino (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
We study the underground economy in a dynamic and stochastic general equilibrium framework. Our model combines limited tax enforcement with an otherwise standard two-sector neoclassical stochastic growth model. The Bayesian estimation of the model based on Italian data provides evidence in favor of an important underground sector in Italy, with a size that has steadily increased over the whole sample period. We show that this pattern is due to a persistent increase in taxation. Fiscal policy experiments suggest that a moderate tax cut, along with a stronger effort in the monitoring process, causes a sensitive reduction in the size of the underground economy and positive stimulus to the regular sector that jointly increase the total fiscal revenues.
Keywords: E65; O41; O52; 330